2018
DOI: 10.7566/jpsj.87.024702
|View full text |Cite
|
Sign up to set email alerts
|

Pyrochlore Oxide Superconductor Cd2Re2O7Revisited

Abstract: The superconducting pyrochlore oxide Cd2Re2O7 is revisited with a particular emphasis on the sample-quality issue. The compound has drawn attention as the only superconductor (Tc = 1.0 K) that has been found in the family of {\alpha}-pyrochlore oxides since its discovery in 2001. Moreover, it exhibits two characteristic structural transitions from the cubic pyrochlore structure, with the inversion symmetry broken at the first one at 200 K. Recently, it has attracted increasing attention as a candidate spin-orb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 97 publications
3
74
1
Order By: Relevance
“…The double SC transition seems to be the evidence that phase VII is the mixtures of phase IV and VIII as discussed in Ref. 11. In addition to the peculiar pressure dependence of T c at zero fields, H c2 enhancement at 4.7 GPa was reproduced through ac susceptibility measurements.…”
mentioning
confidence: 60%
“…The double SC transition seems to be the evidence that phase VII is the mixtures of phase IV and VIII as discussed in Ref. 11. In addition to the peculiar pressure dependence of T c at zero fields, H c2 enhancement at 4.7 GPa was reproduced through ac susceptibility measurements.…”
mentioning
confidence: 60%
“…Images were recorded using a monochrome CCD camera (ST-402ME, SBIG). A pristine (111) crystal surface was observed in a crossed-Nicols setup with a polarizer along [1][2][3][4][5][6][7][8][9][10] and with an analyzer along in most observations; if not mentioned specifically, the direction is based on the cubic structure of phase I. A crystal was attached on a sapphire plate with varnish and cooled slowly from room temperature to 8 K in vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…The surface may have been degraded by polishing, which has actually been observed by various measurements in previous studies. 2) We are currently attempting to obtain a crystal with a (001) facet via fine tuning of the crystal growth conditions. Magnetic susceptibility was measured in a magnetic property measurement system 3 (Quantum Design, MPMS3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental study traces back to magnetic monopole order in Cr 2 O 3 , 64) and recent studies found magnetic toroidal order in LiCoPO 4 , 65,66) magnetic quadrupole order in Sr 2 IrO 4 67,68) and Ba(TiO)Cu 4 (PO 4 ) 4 , 69) and odd-parity electric order in Cd 2 Re 2 O 7 . 70,71) Recent theoretical study has also identified magnetic hexadecapole order in BaMn 2 As 2 . 57) Furthermore, a comprehensive group theoretical classification has identified more than 100 compounds as odd-parity magnetic multipole states.…”
Section: Introductionmentioning
confidence: 99%